Graphene oxide-deposited carbon fiber/cement composites for electromagnetic interference shielding application. (1st June 2015) - Chen, Juan; Zhao, Dan; Ge, Heyi; Wang, Jian
Highlights: Graphene oxide-deposited carbon fiber (GO-CF) was obtained. The GO-CF showed good dispersion in water and cement matrix. GO-CF was found to be more effective than CF in providing EMI shielding of cement. SE of GO-CF/cement had a 31% increase than that of CF/cement in the mass of 0.4 wt.%. Abstract: Graphene oxide-deposited carbon fiber (GO-CF) was obtained by introducing GO onto CF surface through electrophoretic deposition method. GO-CF was found to be more effective than CF in providing electromagnetic interference shielding of cement-based composites. With 0.4 wt.% GO-CF and a shield thickness of 5 mm, a shielding effectiveness of 34 dB was attained at X-band region (8.2–12.4 GHz), which had a 31% increase than that of CF/cement (26 dB) in the same mass fraction. The GO-CF is believed a promising filler of cement-based composites for high electromagnetic interference shielding.